Old Cricket - Wheeler, Lisa, 1963-; Goembel, Ponder (New York : Atheneum Books for Young Readers, 2003)
Old Cricket doesn$1 (Bt feel like helping his wife and neighbors to prepare for winter and so he pretends to have all sorts of ailments that require the doctor$1 (Bs care, but hungry Old Crow has other ideas.s
Keywords: Crickets -- Fiction; Crows -- Fiction; Helpfulness -- Fiction; Behavior -- Fiction